Oral Rehabilitation in a Patient with Major Maxillofacial Trauma: A Case Management - Elif Bahar Tuna; Mehmet Ozgen; Abdulkadir Burak Cankaya; Cenk Sen; Koray Gencay (Hindawi Limited, 2012)
Traumatic injuries may cause anatomic deficiencies in soft and hard tissues. These defects often result in the loss of attached mucosa and alveolar processes, which might reduce potential prosthesis support and require bone and skin grafting. As a result of major maxillofacial trauma, complete or partial avulsion of the palate may require extensive surgical and prosthodontic rehabilitation. The appropriate treatment for the maxillary defect demands a multidisciplinary approach by a team which consists of various fields of dentistry and medicine. The planning prostheses should replace not only missing teeth but also lost soft tissues and bone, and they should include the hard palate, residual alveolar ridges, and, in some instances, the soft palate. This paper describes the treatment procedures including plastic surgery operation procedures and prosthetic rehabilitation in a 19-year-old woman after her severe bicycle accident.